2022
DOI: 10.3390/cancers14215450
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA and microRNA Interplay in Colorectal Cancer and Their Effect on the Tumor Microenvironment

Abstract: As the current staging and grading systems are not sufficient to stratify patients for therapy and predict the outcome of the disease, there is an urgent need to understand cancer in its complexity. The mutual relationship between tumour and immune or stromal cells leads to rapid evolution and subsequent genetic and epigenetic changes. Immunoscore has been introduced as a diagnostic tool for colorectal cancer (CRC) only recently, emphasising the role of the specific tumor microenvironment in patient’s prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Distinct lncRNA/miRNA/protein regulatory axes have been described in many tumor subtypes, including colorectal cancer (CRC) [7]. As well, reported by Marie Rajtmaierova and colleagues in a recent issue of Cancers [8], these molecular switches can regulate multiple aspects of tumor biology, such as the tumor microenvironment/TME composition or the resistance to chemotherapy. In this regard, it has been shown that lncRNA SCARNA2, found to be upregulated in CRC tissues, can directly activate the miR-342-3p-EGFR/BCL2 axis for escaping 5-fluorouracil cytotoxicity [9].…”
mentioning
confidence: 90%
“…Distinct lncRNA/miRNA/protein regulatory axes have been described in many tumor subtypes, including colorectal cancer (CRC) [7]. As well, reported by Marie Rajtmaierova and colleagues in a recent issue of Cancers [8], these molecular switches can regulate multiple aspects of tumor biology, such as the tumor microenvironment/TME composition or the resistance to chemotherapy. In this regard, it has been shown that lncRNA SCARNA2, found to be upregulated in CRC tissues, can directly activate the miR-342-3p-EGFR/BCL2 axis for escaping 5-fluorouracil cytotoxicity [9].…”
mentioning
confidence: 90%
“…Changes in the components of TME have a major impact on genitourinary tumor metastasis and lead to poor clinical outcomes. More and more non-coding RNAs (ncRNAs) including microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), are implicated in TME-mediated carcinogenesis, angiogenesis, invasion, metastasis and chemoresistance ( Liu et al, 2021 ; Jiang et al, 2022 ; Rajtmajerová et al, 2022 ; Xu et al, 2022 ). Clarifying the regulatory link between ncRNAs and TME might aid in the development of innovative therapeutic options for genitourinary malignancies, which would be extremely advantageous in improving the prognosis of patients.…”
mentioning
confidence: 99%